2015
DOI: 10.1016/j.msea.2015.03.101
|View full text |Cite
|
Sign up to set email alerts
|

The role of martensitic transformation on bimodal grain structure in ultrafine grained AISI 304L stainless steel

Abstract: In the present study, metastable AISI 304L austenitic stainless steel samples were subjected to different cold rolling reductions from 70% to 93%, followed by annealing at 700 º C for 300 min to form ultrafine grained (UFG) austenite with different grain structures. Transmission electron microscopy (TEM) and nanoindentation were used to characterize the martensitic transformation, in order to relate it to the bimodal distribution of the austenite grain size after subsequent annealing. The results showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 30 publications
(37 reference statements)
5
23
1
Order By: Relevance
“…8. The calculated parameters using equations (4)(5)(6)(7)(8) are summarized in Table 3. Also, the austenite grain size in the stired zone after FSW is finally related to the Zenner-Hollomon parameter in Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…8. The calculated parameters using equations (4)(5)(6)(7)(8) are summarized in Table 3. Also, the austenite grain size in the stired zone after FSW is finally related to the Zenner-Hollomon parameter in Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Meanwhile, their relatively low hardness and yield strength is not sufficient to meet the requirements for some applications [3]. Moving towards ultrafine and nanocrystalline grain structure is one of the most effective ways to improve their mechanical properties, and as a result, ultra-fine grained (UFG) steels are currently being studied worldwide [4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,9,11] The martensite phase is not stable at elevated temperatures and its reversion to fine-grained austenite can occur by annealing at elevated temperatures. [1,16] While the reversion process has received a considerable attention in recent years for enhancement of mechanical properties, [1,[17][18][19][20][21][22] much more works are required on this subject to identify the different stages of microstructural evolution to enable its control during thermomechanical treatment. Moreover, it has been reported that for obtaining a marked grain refinement, [1,11] the availability of great amounts of martensite before reversion might be required.…”
Section: Introductionmentioning
confidence: 99%
“…Talonen and Hänninen [32] found a close correlation between the shear bands and α'-martensite formation. Also, the relation between shear bands and α'-martensite, may be related to blocked-shape martensite structures form by nucleation and coalescence of α'-martensite embryos within a single shear band [33][34][35][36].…”
Section: U N C O R R E C T E D P R O O F Jj Roa Et Al Materials Scmentioning
confidence: 99%